Dispersion

By using a dispersion with fibrous cellulose of 1000 nm or less and an ionic substituent, the issues of poor transparency and curl in conventional fine fibrous cellulose sheets are addressed, resulting in sheets with enhanced transparency and curl resistance.

JP7647568B2Active Publication Date: 2025-03-18OJI HLDG CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021561580
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-27
Filing Date
2020-11-27
Publication Date
2025-03-18
Estimated Expiration
2040-11-27

AI Technical Summary

Technical Problem

Conventional fine fibrous cellulose dispersions result in sheets with poor transparency and curl issues when formed into sheets.

Method used

A dispersion containing fibrous cellulose with a fiber width of 1000 nm or less and an ionic substituent, with a fibrous cellulose content of 3.0% or more by mass and a TI value of 1 to 80,000, which enhances the transparency and curl resistance of the resulting sheet.

Benefits of technology

The proposed dispersion method achieves sheets with excellent transparency and suppressed curling, improving the mechanical properties and appearance of the final product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647568000011
    Figure 0007647568000011
  • Figure 0007647568000012
    Figure 0007647568000012
  • Figure 0007647568000013
    Figure 0007647568000013
Patent Text Reader

Abstract

The present invention addresses the problem of providing a sheet which has excellent transparency, while being suppressed in curling. The present invention relates to a dispersion liquid which contains a fibrous cellulose that has a fiber width of 1,000 nm or less, while having an ionic substituent, wherein: the content of the fibrous cellulose is 3.0% by mass or more relative to the total mass of the dispersion liquid; and the TI value of the dispersion liquid as calculated under the conditions (a) described below is from 1 to 80,000. Conditions (a): The viscosity (η1) of the dispersion liquid at a shear rate of 1 sec-1 and the viscosity (η2) of the dispersion liquid at a shear rate of 1,000 sec-1 are measured with use of a rheometer, and the TI value is calculated by the formula described below. TI value = η1 / η2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dispersion. In particular, the present invention relates to a dispersion containing fine fibrous cellulose. [Background technology]

[0002] Cellulose fibers have been widely used in clothing, absorbent articles, paper products, etc. As cellulose fibers, in addition to fibrous cellulose with a fiber diameter of 10 μm to 50 μm, fine fibrous cellulose with a fiber diameter of 1 μm or less is also known. Fine fibrous cellulose has attracted attention as a new material and has a wide range of applications.

[0003] When producing fine fibrous cellulose, a slurry containing a cellulose raw material is subjected to a defibration treatment (mechanical treatment). For example, Patent Document 1 discloses a method for producing fine fibers that includes a step of treating the cellulose raw material with an enzyme and a step of defibrating the cellulose raw material after the enzyme treatment. In this method, it is considered that the cellulose raw material is sufficiently finely divided by the enzyme treatment, thereby increasing the yield of fine fibers. In addition, Patent Document 1 aims to produce fine fibers that are long in fiber length and have a large aspect ratio.

[0004] Patent Document 2 discloses fine fibrous cellulose having an average fiber width of 200 nm or less, a degree of polymerization of 50 to 500, and a specific polar group. In this study, the production of fine fibrous cellulose that is less likely to form aggregates when mixed with an emulsion resin is investigated. In the examples of Patent Document 2, a dispersion having a degree of polymerization of 248 to 454 and a viscosity of 108 to 740 at a concentration of 0.5% is obtained. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2013 / 176033 [Patent Document 2] JP 2014-34673 A Summary of the Invention [Problem to be solved by the invention]

[0006] The use of dispersions containing fine fibrous cellulose is diverse, and various processing methods thereof have been studied. For example, forming a sheet containing fine fibrous cellulose by coating or papermaking with the fine fibrous cellulose dispersion has been studied. However, the present inventors have found that when a sheet is formed from a conventional fine fibrous cellulose dispersion, the transparency of the obtained sheet is poor and the sheet curls.

[0007] Therefore, in order to solve such problems of the conventional techniques, the present inventors have carried out studies with the aim of providing a sheet which is excellent in transparency and which is suppressed from curling. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the inventors have found that in a dispersion containing fibrous cellulose having a fiber width of 1000 nm or less and having an ionic substituent, a sheet having excellent transparency and suppressed curling can be obtained by setting the content of fibrous cellulose to 3.0 mass% or more relative to the total mass of the dispersion and setting the TI value of the dispersion to 1 or more and 80,000 or less. Specifically, the present invention has the following configuration.

[0009] [1] A dispersion containing fibrous cellulose having a fiber width of 1000 nm or less and having an ionic substituent, The content of fibrous cellulose is 3.0% by mass or more based on the total mass of the dispersion, A dispersion having a TI value of 1 or more and 80,000 or less, calculated according to the following condition (a): Condition (a): Using a rheometer, the shear rate of the dispersion was 1 sec -1Viscosity (η1) under the condition of and the shear rate of the dispersion of 1000 sec -1 The viscosity (η2) under the above conditions is measured, and the TI value is calculated using the following formula. TI value = η1 / η2 [2] The dispersion according to [1], wherein the content of fibrous cellulose is 4.0 mass% or more based on the total mass of the dispersion. [3] The dispersion according to [1], wherein the content of fibrous cellulose is 5.0 mass% or more based on the total mass of the dispersion. [4] The dispersion according to [1], wherein the content of fibrous cellulose is 6.0% by mass or more based on the total mass of the dispersion. [5] The dispersion liquid according to any one of [1] to [4], wherein the ionic substituent is at least one selected from the group consisting of a phosphorus oxoacid group, a substituent derived from a phosphorus oxoacid group, a sulfur oxoacid group, and a substituent derived from a sulfur oxoacid group. [6] The dispersion according to any one of [1] to [5], wherein the haze of the dispersion at a concentration of 0.2 mass % is 95% or less. [7] A sheet formed from the dispersion according to any one of [1] to [6]. Effect of the Invention

[0010] According to the present invention, a sheet having excellent transparency and suppressed curling can be obtained. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram for explaining a method for evaluating the curl resistance of a sheet. [Diagram 2] FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Diagram 3] FIG. 3 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The following description of the components may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments.

[0013] (dispersion) The dispersion containing fibrous cellulose of this embodiment is a dispersion containing fibrous cellulose having a fiber width of 1000 nm or less and an ionic substituent, in which the content of the fibrous cellulose is 3.0 mass% or more relative to the total mass of the dispersion, and the TI value of the dispersion calculated under the following condition (a) is 1 or more and 80,000 or less. Condition (a): Using a rheometer, the shear rate of the dispersion was 1 sec -1 Viscosity (η1) under the condition of and shear rate of the dispersion of 1000 sec -1 The viscosity (η2) under the above conditions is measured, and the TI value is calculated using the following formula. TI value = η1 / η2

[0014] In this specification, fibrous cellulose having a fiber width of 1000 nm or less is also referred to as fine fibrous cellulose. A dispersion containing fine fibrous cellulose is also referred to as a fine fibrous cellulose dispersion, a fine fibrous cellulose-containing dispersion, or a fine fibrous cellulose-containing slurry.

[0015] Since the dispersion of the present embodiment has the above-mentioned configuration, a sheet having excellent transparency and suppressed curling can be formed. Conventionally, in a dispersion containing 3.0% by mass or more of fine fibrous cellulose, the viscosity is high, so that it is not possible to form a sheet from such a dispersion, or even if a sheet is formed, the sheet has a large curl width. In addition, the formed sheet may have poor transparency. However, in the present embodiment, the concentration of the fine fibrous cellulose dispersion is made high, and the TI value of such a high-concentration dispersion is controlled within a predetermined range, thereby successfully increasing the transparency and curl resistance of the sheet formed from the dispersion. Thus, when a sheet is formed from the dispersion of the present embodiment, a highly transparent sheet with suppressed curling is obtained.

[0016] In the sheet formed from the dispersion of this embodiment, the occurrence of curling is suppressed. That is, the sheet formed from the dispersion of this embodiment has excellent curl resistance. When evaluating curl resistance, a sheet for evaluation is first formed. Specifically, a coating liquid is prepared by mixing solutions in which each component is dispersed so that the solid content mass of the fine fibrous cellulose is 100 parts by mass and the solid content mass of the polyethylene oxide is 20 parts by mass. Next, the coating liquid is measured so that the finished thickness of the obtained sheet (a layer composed of the solid content of the coating liquid) is 40 μm, and a sheet is formed. Next, the obtained fine fibrous cellulose-containing sheet is cut into a test piece having a width of 15 mm and a length of 130 mm, and as shown in FIG. 1, the end including one short side of the test piece 50 is supported by a curl test jig 55 having a width of 30 mm, a length of 30 mm and a height of 25 mm (a test piece having a length of 100 mm is exposed from the jig), and the test piece is placed on a horizontal table in an environment of a temperature of 23° C. and a relative humidity of 50% so that the width direction of the test piece is perpendicular to the table (so that the longitudinal direction of the test piece is parallel to the table). Then, the curl width of the end of the test piece 50 is measured and defined as the curl width C0 (the distance of C0 in FIG. 1). After leaving it for 24 hours, the curl width is measured again and defined as C1 (the distance of C1 in FIG. 1), and C1-C0 is defined as the curl amount. When the value of the curl amount C1-C0 is calculated from the curl width measured in this way, C1-C0 is preferably 25 mm or less, more preferably 5 mm or less. It should be noted that C1-C0 may be 0 mm. When the curl is 25 mm or less, the sheet can be judged to have excellent curl resistance.

[0017] The dispersion of the present embodiment is not limited to use as a sheet, and is expected to have further expanded uses as a high-concentration dispersion.

[0018] In addition, since the dispersion of the present embodiment contains fine fibrous cellulose at a high concentration, the storage cost and transportation cost can be significantly reduced. Conventionally, the concentration of fine fibrous cellulose in a dispersion containing fine fibrous cellulose was about 2% by mass. On the other hand, in the dispersion of the present embodiment, the content of fine fibrous cellulose can be increased to a high concentration of 3.0% by mass or more, which allows a significant reduction in the storage cost and transportation cost, and further increases the production efficiency of the dispersion.

[0019] The content of the fine fibrous cellulose may be 3.0% by mass or more, preferably 4.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 6.0% by mass or more, based on the total mass of the dispersion. The upper limit of the content of the fine fibrous cellulose in the dispersion is not particularly limited, but may be, for example, 20% by mass. Thus, the dispersion of this embodiment is a high-concentration fine fibrous cellulose dispersion. By setting the content of the fine fibrous cellulose in the dispersion within the above range, when a sheet is formed from the dispersion, the curl resistance of the sheet can be more effectively improved. This is thought to be because the amount of moisture carried over to the sheet manufacturing process can be reduced by forming a sheet from a high-concentration fine fibrous cellulose dispersion, which can suppress the occurrence of thermal shrinkage during heating.

[0020] The TI value of the dispersion may be 1 or more, preferably 10 or more, more preferably 30 or more, even more preferably 50 or more, even more preferably 70 or more, and particularly preferably 100 or more. The TI value of the dispersion may be 80,000 or less, preferably 70,000 or less, more preferably 50,000 or less, even more preferably 30,000, and particularly preferably 20,000 or less. By setting the TI value of the dispersion within the above range, when a sheet is formed from the dispersion, the curl resistance of the sheet can be more effectively improved. In addition, by setting the TI value of the dispersion within the above range, when a sheet is produced from the dispersion, the degree of spreading of the dispersion can be appropriately controlled while providing appropriate flowability, so that a uniform sheet can be produced even with a high concentration dispersion.

[0021] Here, the TI value of the dispersion is a value calculated according to the following condition (a). Condition (a): Using a rheometer, the shear rate of the dispersion was 1 sec -1 Viscosity (η1) under the condition of and shear rate of the dispersion of 1000 sec -1 The viscosity (η2) under the above conditions is measured, and the TI value is calculated using the following formula. TI value = η1 / η2 Specifically, the viscosity (η1) and the viscosity (η2) are measured under the following conditions: As a rheometer used for the measurement, for example, RheoStress6000 manufactured by HAAKE can be used. Measurement temperature: 23℃ Measurement tool: Cone plate (diameter 40 mm, angle 1°) Shear rate: 0.001 to 1000 sec -1 Number of data points: 100 Data distribution: Log interval Measurement time: 5 minutes

[0022] Dispersion shear rate: 1 sec -1The viscosity (η1) under these conditions is preferably 1 Pa·s or more, more preferably 10 Pa·s or more, and even more preferably 50 Pa·s or more. Shear rate: 1 sec -1 The viscosity (η1) under these conditions is preferably 5,000 Pa·s or less, more preferably 4,000 Pa·s or less, and even more preferably 3,000 Pa·s or less. In addition, when the shear rate of the dispersion is 1000 sec -1 The viscosity (η2) under these conditions is preferably 0.007 Pa·s or more, more preferably 0.01 Pa·s or more, and even more preferably 0.05 Pa·s or more. Shear rate: 1000 sec -1 The viscosity (η2) under this condition is preferably 100 Pa·s or less, more preferably 50 Pa·s or less, and even more preferably 10 Pa·s or less.

[0023] The haze of the dispersion liquid at a concentration of 0.2% by mass is preferably 95% or less, more preferably 90% or less, even more preferably 80% or less, even more preferably 70% or less, even more preferably 50% or less, even more preferably 30% or less, particularly preferably 10% or less, and most preferably 5% or less. The haze of the dispersion liquid at a concentration of 0.2% by mass may be 0%. When measuring the haze of the dispersion liquid, the haze is measured after adjusting the concentration of the fine fibrous cellulose to 0.2% by mass. The haze of the dispersion liquid is measured by putting the dispersion liquid adjusted to a concentration of 0.2% by mass into a glass cell for liquids (manufactured by Fujiwara Seisakusho, MG-40, reverse light path) with an optical path length of 1 cm, and using a haze meter (manufactured by Murakami Color Research Laboratory, HM-150) in accordance with JIS K 7136:2000. The dispersion liquid to be measured is left to stand for 24 hours in an environment of 23°C and relative humidity of 50% before measurement. In addition, the zero point measurement in the haze measurement is performed with ion-exchanged water placed in the same glass cell. By setting the haze of the dispersion with a concentration of 0.2% by mass within the above range, a sheet with excellent transparency can be easily formed.

[0024] When measuring the viscosity of the dispersion, the fine fibrous cellulose dispersion is measured without dilution. The viscosity of the dispersion is measured using a Brookfield viscometer at 23° C., a rotation speed of 0.3 rpm, and a viscosity value 3 minutes after the start of measurement. As the Brookfield viscometer, for example, a digital viscometer DV2T can be used.

[0025] The viscosity of the dispersion liquid at a concentration of 3.0% by mass is preferably 10 million mPa·s or less, more preferably 9 million mPa·s or less, and even more preferably 8 million mPa·s or less. Also, the viscosity of the dispersion liquid at a concentration of 3.0% by mass is preferably 100,000 mPa·s or more, more preferably 200,000 mPa·s or more, and even more preferably 300,000 mPa·s or more. The viscosity of the dispersion liquid at a concentration of 6.0% by mass is preferably 50 million mPa·s or less, more preferably 30 million mPa·s or less, and even more preferably 20 million mPa·s or less. Also, the viscosity of the dispersion liquid at a concentration of 6.0% by mass is preferably 500,000 mPa·s or more, more preferably 700,000 mPa·s or more, and even more preferably 1 million mPa·s or more. The viscosity of the dispersion liquid at a concentration of 13.0% by mass is preferably 100 million mPa·s or less, more preferably 50 million mPa·s or less, and even more preferably 30 million mPa·s or less. Also, the viscosity of the dispersion liquid at a concentration of 13.0% by mass is preferably 1 million mPa·s or more, more preferably 5 million mPa·s or more, and even more preferably 10 million mPa·s or more.

[0026] The dispersion liquid of the present embodiment is preferably a dispersion liquid containing fine fibrous cellulose and a dispersion medium. The dispersion medium is not particularly limited, but preferably contains water, and more preferably is a solvent containing water as a main component. That is, the dispersion liquid of the present embodiment is preferably an aqueous dispersion liquid containing fine fibrous cellulose. The dispersion medium may be an organic solvent. Examples of the organic solvent include dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), aniline, pyridine, quinoline, lutidine, acetonitrile, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dioxane, ethanol, and isopropanol. In addition, a mixed solvent obtained by mixing these organic solvents with water can also be used as the dispersion medium.

[0027] The dispersion of this embodiment is a high-concentration dispersion containing 3.0% by mass or more of fine fibrous cellulose, but is a dispersion obtained without going through a concentration process. The dispersion of this embodiment is also distinguished from, for example, a dispersion obtained by redispersing a solid body of fine fibrous cellulose. That is, the dispersion of this embodiment is neither a concentrated dispersion nor a concentrated and reduced dispersion. The dispersion of this embodiment is the dispersion itself obtained through a defibration process as described below. Therefore, the dispersion of this embodiment does not contain components involved in concentration and concentration reduction, such as a flocculant.

[0028] Here, in the prior art, it has been considered to increase the concentration of fine fibrous cellulose by adding a flocculant to the dispersion or by concentrating it by heating. However, the present inventors have found that when a flocculant or concentrating it by heating is used in this way, the fine fibrous cellulose aggregates unevenly, and in some cases, aggregates are formed, so that the TI value of the dispersion exceeds 80,000. In addition, even in the dispersion obtained by redispersing the aggregates, the fine fibrous cellulose is dispersed unevenly, so that the TI value of the dispersion cannot be set within the desired range.

[0029] In addition, in the conventional technology, it is difficult to obtain an aqueous dispersion having a high concentration of 3.0% by mass or more, and it is impossible to obtain an aqueous dispersion having a high concentration of 6.0% by mass or 13.0% by mass. Even if the fine fibrous cellulose dispersion obtained in the conventional technology is concentrated to obtain an aqueous dispersion having a concentration of 6.0% by mass or 13.0% by mass, the aqueous dispersion becomes gel-like, or granular matter (fiber aggregates) or the like is generated in the aqueous dispersion, making it impossible to obtain a uniform aqueous dispersion. Naturally, it is impossible to measure the viscosity of such a high-concentration aqueous dispersion. For example, when an aqueous dispersion having a concentration of 0.5 to 2.0% by mass is subjected to a defibration treatment and then concentrated by a heating treatment or an evaporator, a film-like matter is generated on the wall surface during the concentration process, making it impossible to obtain a dispersion having a uniform dispersion of 6.0% by mass or more in which fine fibrous cellulose is dispersed. For this reason, it is impossible to obtain an aqueous dispersion with a high concentration such as 6.0% by mass or 13.0% by mass, and it is not possible to obtain a dispersion having a viscosity within the above range in an aqueous dispersion with a high concentration such as 6.0% by mass or 13.0% by mass.

[0030] On the other hand, in this embodiment, since a dispersion obtained without a concentration process is used, a highly uniform dispersion can be obtained. In addition, the TI value of the dispersion can be set to a range of 1 to 80,000. Therefore, when a sheet is formed from the dispersion of this embodiment, for example, a sheet with high transparency and excellent curl resistance can be obtained. In addition, in this embodiment, the dispersion of phosphorylated pulp to be subjected to the defibration treatment is made highly concentrated, and the defibration treatment is performed on such a high-concentration pulp dispersion, and if necessary, a low-molecular-weight treatment as described below is also performed. This makes it possible to measure the viscosity of an aqueous dispersion containing 3.0% by mass or more of fine fibrous cellulose (for example, an aqueous dispersion containing 6.0% by mass or 13.0% by mass), and it has been possible to successfully obtain an aqueous dispersion with a relatively low viscosity for a high-concentration dispersion.

[0031] (fibrous cellulose) The dispersion of the present embodiment contains fibrous cellulose having a fiber width of 1000 nm or less. The fiber width of the fibrous cellulose is more preferably 100 nm or less, and even more preferably 8 nm or less.

[0032] The fiber width of fibrous cellulose can be measured, for example, by observation under an electron microscope. The average fiber width of fibrous cellulose is, for example, 1000 nm or less. The average fiber width of fibrous cellulose is, for example, preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the average fiber width of fibrous cellulose 2 nm or more, it is possible to suppress dissolution of cellulose molecules in water, and to more easily realize the effect of improving strength, rigidity, and dimensional stability due to fibrous cellulose. The fibrous cellulose is, for example, monofilamentous cellulose.

[0033] The average fiber width of fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.05% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions.

[0034] (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y.

[0035] For observation images that satisfy the above conditions, the width of the fibers that intersect with lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average value of the read fiber widths is then determined as the average fiber width of the fibrous cellulose.

[0036] The fiber length of the fibrous cellulose is not particularly limited, but is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. By setting the fiber length within the above range, destruction of the crystalline region of the fibrous cellulose can be suppressed. In addition, it is also possible to set the slurry viscosity of the fibrous cellulose to an appropriate range. The fiber length of the fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, or AFM.

[0037] The fibrous cellulose preferably has an I-type crystal structure. Here, the fact that the fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This can be expected to provide even more excellent performance in terms of heat resistance and low linear thermal expansion coefficient. The degree of crystallinity can be determined by measuring the X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).

[0038] The axial ratio (fiber length / fiber width) of fibrous cellulose is not particularly limited, but is preferably, for example, 30 or more and 10,000 or less, and more preferably 50 or more and 1,000 or less. In this specification, fibrous cellulose with a fiber width of 1,000 nm or less (fine fibrous cellulose) is cellulose nanofiber (CNF), and fibrous cellulose (fine fibrous cellulose) does not include cellulose nanocrystal (CNC). The axial ratio (fiber length / fiber width) of cellulose nanocrystal (CNC) is usually It is about 10 or more and 30 or less. In addition, by making the axial ratio of the fibrous cellulose equal to or more than the above lower limit, it is preferable in that, for example, when the fibrous cellulose is treated as an aqueous dispersion, handling such as dilution becomes easier.

[0039] The fibrous cellulose in this embodiment has, for example, both crystalline and non-crystalline regions. Fine fibrous cellulose having both crystalline and non-crystalline regions and having an axial ratio within the above range is realized by the method for producing fine fibrous cellulose described below.

[0040] The fibrous cellulose in this embodiment has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. In this embodiment, it is particularly preferable that the ionic substituent has an anionic group. In addition, it is preferable that the ionic substituent is a group that is linked to the fibrous cellulose via an ester bond. In this case, the ester bond is formed by dehydration condensation between the fibrous cellulose and a compound that becomes the ionic substituent.

[0041] The anionic group as the ionic substituent is preferably at least one selected from a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group (sometimes simply referred to as a phosphorus oxoacid group), a carboxy group or a substituent derived from a carboxy group (sometimes simply referred to as a carboxy group), and a sulfur oxoacid group or a substituent derived from a sulfur oxoacid group (sometimes simply referred to as a sulfur oxoacid group), more preferably at least one selected from a phosphorus oxoacid group and a carboxy group, and particularly preferably a phosphorus oxoacid group. By introducing a phosphorus oxoacid group as an ionic substituent into fibrous cellulose, it becomes easier to obtain a dispersion with high transparency, and as a result, it becomes easier to obtain a sheet with excellent transparency. In addition, by introducing a phosphorus oxoacid group into fibrous cellulose, the salt resistance of the fibrous cellulose can also be improved.

[0042] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of types of the substituent represented by the following formula (1) may be introduced into each fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.

[0043] [ka]

[0044] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of the n α and α' is O. - and the rest are R or OR. Note that all of α and α' are O - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances.

[0045] Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In formula (1), n ​​is preferably 1.

[0046] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.

[0047] In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO - ), a functional group in which at least one selected from functional groups such as a hydroxyl group, an amino group, and an ammonium group is added or substituted, but is not particularly limited. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set to an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine cellulose fibers. Note that when there are multiple Rs in formula (1) or when multiple types of substituents represented by the above formula (1) are introduced into the fibrous cellulose, the multiple Rs may be the same or different.

[0048] β b+is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. In addition, in formula (1), β b+ When a plurality of substituents represented by the above formula (1) are present or when a plurality of substituents represented by the above formula (1) are introduced into the fibrous cellulose, the plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.

[0049] More specifically, examples of the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group include a phosphoric acid group (-PO3H2), a salt of a phosphoric acid group, a phosphorous acid group (phosphonic acid group) (-PO2H2), and a salt of a phosphorous acid group (phosphonic acid group). In addition, the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group in which a phosphoric acid group is condensed (e.g., a pyrophosphate group), a group in which a phosphonic acid is condensed (e.g., a polyphosphonic acid group), a phosphoric ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.

[0050] The sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group) is, for example, a substituent represented by the following formula (2). A plurality of substituents represented by the following formula (2) may be introduced into each fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.

[0051] [ka]

[0052] In the above structural formula, b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different. In the above structural formula, β b+ is a monovalent or higher cation made of an organic or inorganic substance. Examples of the monovalent or higher cation made of an organic substance include organic onium ions. Examples of the organic onium ions include organic ammonium ions and organic phosphonium ions. Examples of the organic ammonium ions include aliphatic ammonium ions and aromatic ammonium ions, and examples of the organic phosphonium ions include aliphatic phosphonium ions and aromatic phosphonium ions. Examples of the monovalent or higher cation made of an inorganic substance include ions of alkali metals such as sodium, potassium, and lithium, ions of divalent metals such as calcium and magnesium, hydrogen ions, and ammonium ions. When multiple types of substituents represented by the above formula (2) are introduced into the fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.

[0053] The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 0.10 mmol / g or more per 1 g (mass) of fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.60 mmol / g or more, even more preferably 0.90 mmol / g or more, and particularly preferably 1.00 mmol / g or more. In particular, when the amount of ionic substituent introduced into fibrous cellulose is 1.00 mmol / g or more, the load during defibration can be reduced, and the transparency of the resulting fine fibrous cellulose dispersion or sheet can be further increased. In addition, when the amount of ionic substituent introduced into fibrous cellulose is 1.00 mmol / g or more, the salt tolerance of fibrous cellulose can also be improved. The amount of ionic substituent introduced into the fibrous cellulose is, for example, preferably 5.20 mmol / g or less per gram (mass) of fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, and particularly preferably 1.50 mmol / g or less. Here, the denominator in the unit mmol / g is calculated based on the fact that the counter ion of the ionic substituent is a hydrogen ion (H + ) indicates the mass of fibrous cellulose when the amount of ionic substituent introduced is within the above range. By setting the amount of ionic substituent introduced within the above range, it is possible to easily micronize the fiber raw material and to increase the stability of the fibrous cellulose. Furthermore, by setting the amount of ionic substituent introduced within the above range, it is easy to obtain a dispersion that contains a high concentration of fine fibrous cellulose and has a haze value within a predetermined range.

[0054] The amount of ionic substituents introduced into the fibrous cellulose can be measured, for example, by neutralization titration, in which an alkali such as an aqueous sodium hydroxide solution is added to a slurry containing the obtained fibrous cellulose to determine the change in pH, thereby measuring the amount introduced.

[0055] 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 2 is obtained. In the titration curve shown in the upper part of Figure 2, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 2, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH with respect to the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxoacid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxoacid group introduced (or the amount of phosphorus oxoacid group), it refers to the amount of the first dissociated acid. In FIG. 2, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.

[0056] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)

[0057] 3 is a graph showing the relationship between the amount of NaOH dropped onto a dispersion containing fibrous cellulose having a carboxy group as an ionic substituent and the pH. The amount of carboxy group introduced into the fibrous cellulose is measured, for example, as follows. First, a dispersion liquid containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, a defibration treatment similar to the defibration treatment step described below may be performed on the measurement target prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve as shown in the upper part of FIG. 3 is obtained. In the titration curve shown in the upper part of FIG. 3, the measured pH is plotted against the amount of added alkali, and in the titration curve shown in the lower part of FIG. 3, the increment (differential value) (1 / mmol) of pH against the amount of added alkali is plotted. In this neutralization titration, one point where the increment (differential value of pH against the amount of added alkali) is maximum is confirmed in the curve plotting the measured pH against the amount of added alkali, and this maximum point is called the first end point. Here, the region from the start of titration to the first end point in FIG. 3 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the dispersion used for titration. The amount of alkali required in the first region of the titration curve (mmol) is divided by the solid content (g) in the dispersion containing the fibrous cellulose to be titrated to calculate the amount of carboxyl groups introduced (mmol / g).

[0058] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated by the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)

[0059] In measuring the amount of ionic substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of ionic substituents may be lower than the actual amount, and an accurate value may not be obtained. As an appropriate amount of drop and titration interval, for example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.

[0060] The amount of sulfur oxoacid groups introduced into fibrous cellulose can be calculated by wet ashing a slurry containing fibrous cellulose, diluting the sample at an appropriate ratio, and measuring the amount of sulfur. Specifically, fibrous cellulose is wet ashed using perchloric acid and concentrated nitric acid, then diluted at an appropriate ratio and the amount of sulfur is measured by ICP emission spectrometry. The value divided by the bone dry mass of the fibrous cellulose used is taken as the amount of sulfur oxoacid groups (unit: mmol / g).

[0061] The degree of polymerization of the fine fibrous cellulose is preferably not more than 800, more preferably not more than 700, even more preferably not more than 450, and particularly preferably not more than 300. The degree of polymerization of the fibrous cellulose is preferably not less than 100, and more preferably not less than 150. By setting the degree of polymerization of the fine fibrous cellulose within the above range, it becomes easier to obtain a dispersion having a TI value within a predetermined range while containing a high concentration of fine fibrous cellulose.

[0062] The degree of polymerization of fine fibrous cellulose is a value calculated from the pulp viscosity measured according to Tappi T230. Specifically, the fine fibrous cellulose to be measured is dispersed in an aqueous copper ethylenediamine solution to measure the viscosity (referred to as ηX), and the blank viscosity (referred to as η0) is measured using only the dispersion medium, and then the specific viscosity (ηsp) and intrinsic viscosity ([η]) are measured according to the following formula. ηsp=(ηX / η0)-1 [η]=ηsp / (c(1+0.28×ηsp)) Here, c in the formula represents the concentration of the fine fibrous cellulose at the time of viscosity measurement. Furthermore, the degree of polymerization (DP) is calculated from the following formula. DP = 1.75 × [η] Since this degree of polymerization is an average degree of polymerization measured by a viscosity method, it is sometimes called the "viscosity average degree of polymerization."

[0063] The above describes the fibrous cellulose and the dispersion containing the fibrous cellulose according to the present embodiment. In addition, in the present specification, as another embodiment, there is provided a dispersion containing fine fibrous cellulose having a fiber width of 1000 nm or less and an ionic substituent, in which the content of the fine fibrous cellulose is 5.0 mass% or more and 14.0 mass% or less with respect to the total mass of the dispersion, the polymerization degree of the fine fibrous cellulose is 165 or more and 290 or less, and the shear rate of the dispersion measured using a rheometer is 1 sec -1 The viscosity (η1) under the above condition is 60 Pa·s or more and 830 Pa·s or less, and the shear rate of the dispersion is 1000 sec -1 Also disclosed is a dispersion containing fine fibrous cellulose, in which the viscosity (η2) under the above conditions is 0.02 Pa·s or more and 0.56 Pa·s or less. The ionic substituent is particularly preferably a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group (among which, a phosphate group). The amount of ionic substituent introduced into the fine fibrous cellulose is particularly preferably 0.90 mmol / g or more and 2.00 mmol / g or less. The rest of the description is the same as that of the dispersion containing fibrous cellulose according to the present embodiment described above, and will not be repeated here.

[0064] (Method of producing fine fibrous cellulose) <Textile raw materials> Fine fibrous cellulose is produced from a fiber raw material containing cellulose (cellulose fiber). The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited, chemical pulps such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), hardwood dissolving pulp (LDKP, LDSP), softwood dissolving pulp (NDKP, NDSP), soda pulp (AP), unbleached kraft pulp (UKP) and oxygen bleached kraft pulp (OKP), semi-chemical pulps such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), mechanical pulps such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), etc. Examples of non-wood pulps include, but are not limited to, cotton-based pulps such as cotton linters and cotton lint, and non-wood pulps such as hemp, straw, and bagasse. Examples of deinked pulps include, but are not limited to, deinked pulps made from waste paper. The pulps of this embodiment may be used alone or in combination of two or more. Among the above pulps, wood pulp and deinked pulp are preferred from the viewpoint of ease of availability. Among wood pulps, chemical pulps are more preferred, and kraft pulp and sulfite pulp are even more preferred, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and a small decomposition of cellulose in the pulp and a high axial ratio of long fibers. Among them, pulps derived from coniferous trees are preferably used because they have good defibration properties during defibration treatment described below and have improved transparency when made into a dispersion.

[0065] As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Also, instead of a fiber raw material containing cellulose, a fiber formed by a linear nitrogen-containing polysaccharide polymer such as chitin or chitosan can be used.

[0066] <Phosphorus oxo acid group introduction step> The process for producing fine fibrous cellulose includes a step of introducing an ionic substituent. An example of the step of introducing an ionic substituent is a step of introducing a phosphorus oxoacid group. The step of introducing a phosphorus oxoacid group is a step of reacting a hydroxyl group in a fiber raw material containing cellulose with at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing a phosphorus oxoacid group, on the fiber raw material containing cellulose. This step results in the production of a fiber into which a phosphorus oxoacid group has been introduced.

[0067] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B.

[0068] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. Compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.

[0069] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of the phosphoric acid include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high efficiency of introduction of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, or ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, or phosphorous acid and sodium phosphite are more preferred.

[0070] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.

[0071] As described above, the compound B used in this embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use an aqueous solution of compound B. Also, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.

[0072] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is preferably, for example, 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.

[0073] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.

[0074] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that allows efficient introduction of the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, or a high-frequency dryer.

[0075] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, followed by heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like, can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A).

[0076] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated in the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.

[0077] The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.

[0078] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be carried out twice or more. By carrying out the phosphorus oxo acid group introduction step twice or more, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material.

[0079] The amount of phosphorus oxo acid groups introduced into the fiber raw material is preferably 0.10 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.60 mmol / g or more, even more preferably 0.90 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of phosphorus oxo acid groups introduced into the fiber raw material is preferably 5.20 mmol / g or less per 1 g (mass) of fine fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, and particularly preferably 1.50 mmol / g or less. By setting the amount of phosphorus oxo acid groups introduced within the above range, it is possible to easily fine the fiber raw material and increase the stability of the fine fibrous cellulose. In addition, by setting the amount of phosphorus oxoacid groups to within the above range, it becomes easier to obtain a dispersion containing fine fibrous cellulose at a high concentration and having a haze value within a predetermined range. In addition, by setting the amount of phosphorus oxoacid groups to 1.00 mmol / g or more, it is possible to improve the salt tolerance of the fibrous cellulose.

[0080] <Carboxy group introduction step> The process for producing fine fibrous cellulose may include, for example, a carboxyl group introduction step as an ionic substituent introduction step. The carboxyl group introduction step is carried out by subjecting a fiber raw material containing cellulose to an oxidation treatment such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride of a compound having a carboxylic acid-derived group or a derivative thereof.

[0081] Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.

[0082] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.

[0083] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of pH 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). By further allowing sodium chlorite to coexist, aldehydes generated during the oxidation process can be efficiently oxidized to carboxyl groups. The TEMPO oxidation treatment may also be performed under conditions of pH 10 or more and 11 or less. Such a treatment is also called an alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be performed, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a cocatalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.

[0084] The amount of carboxyl groups introduced into the fibrous cellulose varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, it is preferably 0.10 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.60 mmol / g or more, even more preferably 0.90 mmol / g or more, and particularly preferably 1.00 mmol / g or more. In addition, the amount of carboxyl groups introduced into the fibrous cellulose is preferably 3.65 mmol / g or less, more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, and even more preferably 1.50 mmol / g or less. In addition, when the substituent is a carboxymethyl group, it may be 5.8 mmol / g or less per 1 g (mass) of fine fibrous cellulose. By controlling the amount of carboxyl groups introduced within the above range, it is possible to easily pulverize the fiber raw material and to increase the stability of the fibrous cellulose. Also, by controlling the amount of carboxyl groups introduced within the above range, it is possible to easily obtain a dispersion having a haze value within a predetermined range while containing a high concentration of fine fibrous cellulose.

[0085] <Sulfur oxoacid group introduction step> The process for producing fine fibrous cellulose may include, for example, a sulfur oxoacid group introduction step as an ionic substituent introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain cellulose fibers having sulfur oxoacid groups (sulfur oxoacid group-introduced fibers).

[0086] In the sulfur oxo acid group introduction step, instead of compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing sulfur oxo acid groups by reacting with hydroxyl groups of fiber raw materials containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As sulfuric acid, sulfuric acid of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts of sulfates or sulfites may be used, and these may have various degrees of neutralization. As sulfuric acid amides, sulfamic acid or the like may be used. In the sulfur oxo acid group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.

[0087] In the sulfur oxoacid group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a heat-treatment temperature that allows efficient introduction of sulfur oxoacid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat-treatment temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. The heat-treatment temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.

[0088] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, various devices having a heat medium can be used, such as a hot air dryer, a stirring dryer, a rotary dryer, a disk dryer, a roll type heater, a plate type heater, a fluidized bed dryer, a band type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far infrared heater, a microwave heater, and a high frequency dryer.

[0089] The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 0.05 mmol / g or more, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.60 mmol / g or more, even more preferably 0.90 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 5.00 mmol / g or less, more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, and particularly preferably 1.50 mmol / g or less. By setting the amount of sulfur oxoacid groups introduced within the above range, it is possible to easily refine the fiber raw material and increase the stability of the fibrous cellulose. Furthermore, by setting the amount of sulfur oxoacid groups introduced within the above range, it becomes easier to obtain a dispersion having a haze value within a predetermined range while still containing a high concentration of fine fibrous cellulose.

[0090] <Cleaning process> In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.

[0091] <Alkaline treatment process> When producing fine fibrous cellulose, an alkali treatment may be carried out on the fiber raw material between the step of introducing an ionic substituent and the step of defibrating the fiber, which will be described later. The method of the alkali treatment is not particularly limited, but may be, for example, a method of immersing the fiber having an ionic substituent introduced therein in an alkali solution.

[0092] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.

[0093] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5° C. to 80° C., and more preferably from 10° C. to 60° C. The time for immersing the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is, for example, preferably from 5 minutes to 30 minutes, and more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the ionic substituent-introduced fiber.

[0094] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.

[0095] <Acid treatment process> When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described later. For example, the step of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order.

[0096] The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.

[0097] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, from 5° C. to 100° C., and more preferably from 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably from 5 minutes to 120 minutes, and more preferably from 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the fiber raw material.

[0098] <Defibrillation processing> The ionic substituent-introduced fibers are defibrated (mechanically) in a defibration process to obtain fine fibrous cellulose. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.

[0099] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).

[0100] The concentration of cellulose fibers during the defibration process can be appropriately set, but in this embodiment, the concentration of cellulose fibers during the defibration process is preferably 3.0% by mass or more, more preferably 4.0% by mass or more, even more preferably 5.0% by mass or more, and particularly preferably 6.0% by mass or more. The upper limit of the concentration of cellulose fibers during the defibration process is not particularly limited, but may be, for example, 20.0% by mass. In this embodiment, by setting the concentration of cellulose fibers during the defibration process within the above range, a sheet with excellent transparency and suppressed curling can be easily obtained. In addition, by setting the concentration of cellulose fibers during the defibration process within the above range, a highly concentrated dispersion can be obtained, and costs during transportation and storage can also be reduced.

[0101] Furthermore, the slurry obtained by dispersing the ionic substituent-introduced fibers in a dispersion medium may contain solid matters other than the ionic substituent-introduced fibers, such as urea having hydrogen bonding properties.

[0102] <Low viscosity treatment> The method for producing fine fibrous cellulose of the present embodiment preferably includes a step of performing a viscosity reduction treatment in addition to the steps described above. Specifically, as described above, it is preferable to include a step of performing a defibration treatment on cellulose fibers that have been appropriately treated to obtain fibrous cellulose having a fiber width of 1000 nm or less, and a step of performing a viscosity reduction treatment on the fibrous cellulose. That is, the method for producing fine fibrous cellulose of the present embodiment preferably includes, for example, a step of performing a viscosity reduction treatment on cellulose fibers after performing a defibration treatment. Note that the viscosity reduction treatment may be performed before the defibration treatment step, and for example, the viscosity reduction treatment may be performed before the defibration treatment, and then the viscosity reduction treatment may be performed after the defibration treatment. In addition, the viscosity reduction treatment may be performed after the defibration treatment, and then the viscosity reduction treatment may be performed again after the defibration treatment. Among these, it is preferable to perform a viscosity reduction treatment after the defibration treatment in order to reduce the viscosity more effectively.

[0103] The concentration of the fine fibrous cellulose or cellulose fiber during the viscosity reduction treatment can be appropriately set, but it is preferably the same concentration as the concentration of the cellulose fiber during the defibration treatment. For example, the concentration of the fine fibrous cellulose or cellulose fiber during the viscosity reduction treatment is preferably 3.0% by mass or more, more preferably 4.0% by mass or more, even more preferably 5.0% by mass or more, and particularly preferably 6.0% by mass or more. The upper limit of the concentration of the fine fibrous cellulose or cellulose fiber during the viscosity reduction treatment is not particularly limited, but may be, for example, 20.0% by mass. In this embodiment, by setting the concentration of the cellulose fiber during the viscosity reduction treatment within the above range, a sheet with excellent transparency and suppressed curling can be easily obtained.

[0104] Examples of the viscosity-reducing treatment step include an ozone treatment step, an enzyme treatment step, an acid treatment step, a subcritical water treatment step, etc. The viscosity-reducing treatment step is preferably at least one selected from an ozone treatment step, an enzyme treatment step, and an acid treatment step, and more preferably at least one selected from an ozone treatment step and an enzyme treatment step.

[0105] In the ozone treatment step, ozone is added to the fine fibrous cellulose dispersion (slurry). When adding ozone, it is preferable to add it as an ozone / oxygen mixed gas, for example. In this case, the ozone addition rate per 1 g of fine fibrous cellulose contained in the fine fibrous cellulose dispersion (slurry) is 1.0×10 -4 g or more, and 1.0×10 -3 g or more, and more preferably 1.0×10 -2 The ozone addition rate per 1 g of fine fibrous cellulose is preferably 1.0×10 1 After adding ozone to the fine fibrous cellulose dispersion (slurry), it is preferable to stir the mixture at a temperature of 10° C. to 50° C. for 10 seconds to 10 minutes, and then leave the mixture to stand for 1 minute to 100 minutes.

[0106] In the enzyme treatment step, an enzyme is added to the fine fibrous cellulose dispersion (slurry). The enzyme used in this step is preferably a cellulase enzyme. Cellulase enzymes are classified into a carbohydrate hydrolase family based on the higher-order structure of the catalytic domain that has the function of hydrolyzing cellulose. Cellulase enzymes are broadly classified into endo-glucanase and cellobiohydrolase according to their cellulose decomposition properties. Endo-glucanase has high hydrolysis ability for the amorphous part of cellulose, soluble cellooligosaccharides, and cellulose derivatives such as carboxymethylcellulose, and randomly cuts the molecular chains from the inside to reduce the degree of polymerization. In contrast, cellobiohydrolase decomposes the crystalline part of cellulose to give cellobiose. Cellobiohydrolase also hydrolyzes from the end of the cellulose molecule and is also called exo-type or processive enzyme. The enzyme used in the enzyme treatment step is not particularly limited, but it is preferable to use endo-glucanase.

[0107] In the enzyme treatment step, the enzyme is preferably added so that the enzyme activity is 0.1 nkat or more per 1 g of fine fibrous cellulose, more preferably 1.0 nkat or more, and even more preferably 10 nkat or more. The enzyme is preferably added so that the enzyme activity is 100,000 nkat or less per 1 g of fine fibrous cellulose, more preferably 50,000 nkat or less, and even more preferably 10,000 nkat or less. After adding the enzyme to the fine fibrous cellulose dispersion (slurry), it is preferable to treat the dispersion at 0°C or more and less than 80°C for 1 minute to 100 hours, and then to inactivate the enzyme by placing the dispersion at 80°C or more.

[0108] The acid treatment step is, for example, a step of mixing with sulfuric acid, nitric acid, hydrochloric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, boric acid, sulfonic acid (e.g., methanesulfonic acid), etc. Among them, the acid treatment step is preferably a step of mixing with hypochlorous acid (hypochlorite treatment step). In the hypochlorite treatment step, sodium hypochlorite can also be used in the fine fibrous cellulose dispersion (slurry). The addition rate of sodium hypochlorite is 1.0×10 per 1 g of fine fibrous cellulose. -4 g or more, and 1.0×10 -3 g or more, and more preferably 1.0×10 -2 g or more, and more preferably 1.0×10 -1 g or more. The sodium hypochlorite addition rate is particularly preferably 1.0×10 2 After sodium hypochlorite is added to the fine fibrous cellulose dispersion (slurry), stirring is preferably carried out under conditions of 10° C. or higher and 50° C. or lower for 1 minute or longer and 10 hours or shorter.

[0109] It is preferable to further provide a defibration process after the viscosity reduction process. In particular, it is preferable to provide a defibration process before and after the viscosity reduction process. In this case, the defibration process can be exemplified by the same processes as those described above, and in particular, it is preferable to use a high-pressure homogenizer or an ultra-high-pressure homogenizer in the defibration process after the viscosity reduction process.

[0110] The present embodiment may relate to a method for producing fine fibrous cellulose, which includes at least one step each of a step of defibrating cellulose fibers having an ionic substituent and a step of reducing viscosity. The method for producing fine fibrous cellulose includes at least one step each of a step of defibrating cellulose fibers having an ionic substituent and a step of reducing molecular weight, so that the concentration of cellulose fibers during defibration can be further increased. This makes it possible to efficiently obtain a highly concentrated fine fibrous cellulose dispersion. In this case, the method for producing fine fibrous cellulose may include a defibration process, a viscosity reducing process, and a defibration process in this order, or may include a viscosity reducing process, a defibration process, a viscosity reducing process, and a defibration process in this order. It is preferable that an ionic substituent introduction process, a washing process, an alkali treatment process, or the like, as described above, is provided before the first defibration process or the viscosity reducing process. In such a method for producing fine fibrous cellulose, the viscosity reduction treatment step is preferably at least one selected from an ozone treatment step, an enzyme treatment step, a hypochlorous acid treatment step, and a subcritical water treatment step, and is particularly preferably at least one selected from an ozone treatment step and an enzyme treatment step.

[0111] (Additives) The dispersion of the present embodiment may contain other additives in addition to the fine fibrous cellulose and the dispersion medium as described above. Examples of other additives include defoamers, lubricants, UV absorbers, dyes, pigments, stabilizers, surfactants, and preservatives (e.g., phenoxyethanol). In addition, the fibrous cellulose dispersion may contain hydrophilic polymers, hydrophilic low-molecular-weight compounds, organic ions, and the like as optional components.

[0112] The hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound (excluding the above-mentioned cellulose fibers), and examples of the oxygen-containing organic compound include hydrophilic polymers such as polyethylene glycol, polyethylene oxide, casein, dextrin, starch, modified starch, polyvinyl alcohol, modified polyvinyl alcohol (acetoacetylated polyvinyl alcohol, etc.), polyethylene oxide, polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates, acrylic acid alkyl ester copolymers, urethane copolymers, and cellulose derivatives (hydroxyethyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, etc.).

[0113] The hydrophilic low molecular weight compound is preferably a hydrophilic oxygen-containing organic compound, more preferably a polyhydric alcohol, such as glycerin, sorbitol, or ethylene glycol.

[0114] Examples of organic ions include tetraalkylammonium ions and tetraalkylphosphonium ions. Examples of tetraalkylammonium ions include tetramethylammonium ions, tetraethylammonium ions, tetrapropylammonium ions, tetrabutylammonium ions, tetrapentylammonium ions, tetrahexylammonium ions, tetraheptylammonium ions, tributylmethylammonium ions, lauryltrimethylammonium ions, cetyltrimethylammonium ions, stearyltrimethylammonium ions, octyldimethylethylammonium ions, lauryldimethylethylammonium ions, didecyldimethylammonium ions, lauryldimethylbenzylammonium ions, and tributylbenzylammonium ions. Examples of tetraalkylphosphonium ions include tetramethylphosphonium ions, tetraethylphosphonium ions, tetrapropylphosphonium ions, tetrabutylphosphonium ions, and lauryltrimethylphosphonium ions. Examples of tetrapropylonium ions and tetrabutylonium ions include tetra-n-propylonium ions and tetra-n-butylonium ions, respectively.

[0115] (Method of producing dispersion liquid) This embodiment may relate to the above-mentioned method for producing a fine fibrous cellulose dispersion. The method for producing a fine fibrous cellulose dispersion includes a step of defibrating cellulose fibers having an ionic substituent (defibration step) and a step of reducing the viscosity (viscosity reduction step). Here, the concentration of the cellulose fibers in the defibration step is preferably 3.0% by mass or more, more preferably 4.0% by mass or more, even more preferably 5.0% by mass or more, and particularly preferably 6.0% by mass or more. Similarly to the above, the concentration of the fine fibrous cellulose or cellulose fibers in the viscosity reduction step is preferably 3.0% by mass or more, more preferably 4.0% by mass or more, even more preferably 5.0% by mass or more, and particularly preferably 6.0% by mass or more.

[0116] The viscosity reducing process may be performed before the defibration process, or after the defibration process. The viscosity reducing process may be performed before or after the defibration process. For example, a viscosity reducing process may be performed before the defibration process, and then a viscosity reducing process may be performed after the defibration process. The viscosity reducing process may be performed after the viscosity reducing process, and then a viscosity reducing process may be performed again after the defibration process. In particular, the viscosity reducing process is preferably performed after the defibration process. Examples of the viscosity reducing process include the processes described above.

[0117] The dispersion production method of this embodiment includes both a defibration process and a viscosity reducing process, and by increasing the concentration of cellulose fibers in the defibration process, it has been possible to successfully obtain a high concentration dispersion with a fibrous cellulose content of 3.0 mass% or more relative to the total mass of the dispersion. Furthermore, in the dispersion production method of this embodiment, by providing a viscosity reducing process in addition to such a defibration process, it is possible to set the TI value of the dispersion to 1 or more and 80,000 or less.

[0118] In the method for producing a dispersion of this embodiment, the concentration of the cellulose fibers in the defibration process is set to 3.0% by mass or more, so that the concentration of the fine fibrous cellulose dispersion obtained after the defibration process can be set to 3.0% by mass or more. Therefore, there is no need to provide a concentration process in the method for producing a dispersion of this embodiment. It is preferable that the method for producing a dispersion of this embodiment does not include a concentration process. Examples of the concentration process include a process of concentrating using a flocculant and a process of concentrating by heating.

[0119] (Application) The dispersion of the present embodiment is a dispersion containing fine fibrous cellulose at a high concentration. Therefore, it is particularly preferably used in applications where fine fibrous cellulose is to be added at a high concentration. For example, the fine fibrous cellulose of the present embodiment can be used as an additive to food, cosmetics, cement, paint (for painting vehicles such as automobiles, ships, and aircraft, for building materials, for daily necessities, etc.), ink, medicine, etc. In addition, the fine fibrous cellulose of the present embodiment can be added to resin-based materials and rubber-based materials.

[0120] In addition, when a sheet or coating film is formed from the dispersion of this embodiment containing a high concentration of fine fibrous cellulose, the mechanical strength of the resulting sheet or coating film can be increased. For example, the tensile strength and tensile modulus of the sheet or coating film can be more effectively increased. Furthermore, since the dispersion of this embodiment is highly transparent, the transparency of the resulting sheet or coating film can also be increased. Thus, the fine fibrous cellulose dispersion of this embodiment is preferably a dispersion for forming a sheet, and this embodiment may relate to a sheet containing the above-mentioned fine fibrous cellulose.

[0121] Furthermore, when a sheet or coating film is formed from the dispersion liquid of this embodiment containing a high concentration of fine fibrous cellulose, a sheet or coating film with a high basis weight can be obtained.

[0122] When producing a sheet from the dispersion of the present embodiment, it is preferable to include a coating step of coating the dispersion on a substrate, or a papermaking step of making paper from the dispersion.

[0123] In the coating process, for example, a slurry (coating liquid) containing fibrous cellulose is coated on a substrate, and the resulting sheet formed by drying is peeled off from the substrate to obtain a sheet. By using a coating device and a long substrate, sheets can be produced continuously. In addition, the papermaking process is carried out by making paper from the slurry using a papermaking machine. The papermaking machine used in the papermaking process is not particularly limited, and examples thereof include continuous papermaking machines such as Fourdrinier, cylinder, and tilting types, and multi-layer papermaking machines that combine these. In the papermaking process, a known papermaking method such as handmaking may be used.

[0124] A resin layer or an inorganic layer may be further laminated on the sheet formed from the dispersion of this embodiment.

[0125] This embodiment may also have the following configuration. <101> A dispersion containing fine fibrous cellulose having a fiber width of 1000 nm or less and having an ionic substituent, The content of fine fibrous cellulose is 5.0% by mass or more and 14.0% by mass or less based on the total mass of the dispersion, The degree of polymerization of the fine fibrous cellulose is 165 or more and 290 or less, Shear rate of the dispersion measured using a rheometer: 1 sec -1 The viscosity (η1) under the above conditions is 60 Pa s or more and 830 Pa s or less, The shear rate of the dispersion was measured using a rheometer at 1000 sec -1 The viscosity (η2) under the above conditions is 0.02 Pa s or more and 0.56 Pa s or less. A dispersion containing fine fibrous cellulose. <102> The ionic substituent is a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group. <101> The fine fibrous cellulose-containing dispersion according to claim 1. <103> The amount of ionic substituent introduced into the fine fibrous cellulose is 0.90 mmol / g or more and 2.00 mmol / g or less. <101> or <102> The fine fibrous cellulose-containing dispersion according to claim 1.

[0126] <111> A step of subjecting cellulose fibers having ionic substituents to a defibration treatment to obtain fibrous cellulose having a fiber width of 1000 nm or less; and subjecting the fibrous cellulose to a viscosity-reducing treatment, The content of fibrous cellulose is 3.0% by mass or more based on the total mass of the dispersion, A method for producing a fibrous cellulose-containing dispersion, in which the TI value of the dispersion calculated according to the following condition (a) is 1 or more and 80,000 or less; Condition (a): Using a rheometer, the shear rate of the dispersion was 1 sec -1 Viscosity (η1) under the condition of and the shear rate of the dispersion of 1000 sec -1 The viscosity (η2) under the above conditions is measured, and the TI value is calculated using the following formula. TI value = η1 / η2 <112> The concentration of cellulose fibers in the step of obtaining fibrous cellulose having a fiber width of 1000 nm or less by defibration treatment is 3.0% by mass or more. <111> A method for producing a fibrous cellulose-containing dispersion according to claim 1. <113> The step of performing the viscosity reduction treatment is at least one selected from an ozone treatment step, an enzyme treatment step, an acid treatment step, and a subcritical water treatment step. <111> or <112> A method for producing a fibrous cellulose-containing dispersion according to claim 1. <114> The method further includes a step of performing a defibration process after the step of performing the viscosity reduction process. <111> ~ <113> 3. A method for producing a fibrous cellulose-containing dispersion according to any one of claims 1 to 2. <115> <111> ~ <114> 13. A dispersion produced by the method for producing a fibrous cellulose-containing dispersion according to any one of claims 1 to 12. EXAMPLES

[0127] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.

[0128] <Production Example 1> [Production of phosphorylated fine fibrous cellulose dispersion] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 208 g / m) manufactured by Oji Paper. 2 A sheet-like pulp (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated and measured according to JIS P 8121-2:2012) was used. This raw pulp was subjected to phosphorus oxo-oxidation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the total weight to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 200 seconds to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.

[0129] The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.

[0130] Next, the phosphorylated pulp after washing was subjected to a neutralization treatment as follows. First, the phosphorylated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp that had been subjected to a neutralization treatment. Next, the above-mentioned washing treatment was performed on the phosphorylated pulp after the neutralization treatment.

[0131] The infrared absorption spectrum of the phosphorylated pulp obtained was measured using FT-IR. -1 Absorption due to phosphate groups was observed in the vicinity, confirming that phosphate groups had been added to the pulp.

[0132] In addition, the obtained phosphorylated pulp was analyzed using an X-ray diffraction device, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.

[0133] Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 3% by mass. This slurry was treated once with a single-disk refiner (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0134] <Production Example 2> Ion-exchanged water was added to the phosphorylated pulp obtained in Production Example 1 to prepare a slurry with a solid content concentration of 6% by mass. This slurry was treated once with a single-disk refiner (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0135] <Production Example 3> Ion-exchanged water was added to the phosphorylated pulp obtained in Production Example 1 to prepare a slurry with a solid content concentration of 13% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0136] <Production Example 4> Ion-exchanged water was added to the phosphorylated pulp obtained in Production Example 1 to prepare a slurry with a solid content concentration of 6% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0137] <Production Example 5> [Production of TEMPO-oxidized fine fibrous cellulose dispersion] As the raw material pulp, softwood kraft pulp (undried) manufactured by Oji Paper Co., Ltd. was used. This raw material pulp was subjected to an alkaline TEMPO oxidation treatment as follows. First, the raw material pulp equivalent to 100 parts by mass of dry mass, 1.6 parts by mass of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), and 10 parts by mass of sodium bromide were dispersed in 10,000 parts by mass of water. Next, a 13% by mass sodium hypochlorite solution was added so that sodium hypochlorite was 3.8 mmol per 1.0 g of pulp to start the reaction. During the reaction, a 0.5 M aqueous sodium hydroxide solution was added dropwise to keep the pH at 10 to 10.5, and the reaction was deemed to be complete when no change in pH was observed.

[0138] The TEMPO oxidized pulp was then washed. The washing was performed by dehydrating the pulp slurry after TEMPO oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water into the sheet, stirring to disperse the sheet uniformly, and then filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.

[0139] The remaining aldehyde groups in this dehydrated sheet were subjected to additional oxidation treatment as follows: 100 parts by weight of the above dehydrated sheet on a dry basis was dispersed in 10,000 parts by weight of 0.1 mol / L acetate buffer (pH 4.8). Next, 113 parts by weight of 80% by weight sodium chlorite was added, and the container was immediately sealed, and then reacted at room temperature for 48 hours while stirring at 500 rpm using a magnetic stirrer to obtain a pulp slurry.

[0140] Next, the obtained TEMPO oxidized pulp after additional oxidation was subjected to a washing treatment. The washing treatment was carried out by dehydrating the pulp slurry after additional oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water, stirring to disperse uniformly, and then repeatedly filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.

[0141] In addition, the obtained TEMPO oxidized pulp was analyzed using an X-ray diffraction device, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.

[0142] Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid content of 3% by mass. This slurry was treated once with a single disc refiner (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.

[0143] <Production Example 6> Ion-exchanged water was added to the TEMPO oxidized pulp obtained in Production Example 5 to prepare a slurry with a solid content of 6% by mass. This slurry was treated once with a single disc refiner (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a fine fibrous cellulose dispersion containing fine fibrous cellulose. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.

[0144] <Production Example 7> Ion-exchanged water was added to the TEMPO oxidized pulp obtained in Production Example 5 to prepare a slurry with a solid content of 13% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.

[0145] <Production Example 8> Ion-exchanged water was added to the TEMPO oxidized pulp obtained in Production Example 5 to prepare a slurry with a solid content of 6% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.

[0146] <Production Example 9> [Production of Phosphorous Fine Fibrous Cellulose Dispersion] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 245 g / m) manufactured by Oji Paper. 2A sheet-like pulp (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated and measured according to JIS P 8121-2:2012) was used. This raw pulp was subjected to phosphorus oxo-oxidation treatment as follows. First, a mixed aqueous solution of phosphorous acid (phosphonic acid) and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to prepare 33 parts by mass of phosphorous acid (phosphonic acid), 120 parts by mass of urea, and 150 parts by mass of water, thereby obtaining a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 250 seconds to introduce phosphorous acid groups into the cellulose in the pulp, thereby obtaining a phosphorous-saturated pulp.

[0147] The resulting phosphorous-subtilized pulp was then washed. The washing was carried out by repeatedly pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorous-subtilized pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse the pulp, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.

[0148] Next, the washed phosphited pulp was subjected to a neutralization treatment as follows. First, the washed phosphited pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a phosphited pulp slurry having a pH of 12 to 13. Next, the phosphited pulp slurry was dehydrated to obtain a neutralized phosphited pulp. Next, the neutralized phosphited pulp was subjected to the above-mentioned washing treatment.

[0149] The infrared absorption spectrum of the phosphorous pulp obtained was measured using FT-IR. -1Absorption due to the P=O of the phosphonic acid group, which is a tautomer of the phosphorous acid group, was observed near the nucleus, confirming that the phosphorous acid group (phosphonic acid group) was added to the pulp. In addition, when the obtained phosphorous-containing pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, confirming that it has cellulose type I crystals.

[0150] Ion-exchanged water was added to the obtained phosphorous-containing pulp to prepare a slurry with a solid content of 3% by mass. This slurry was treated once with a single-disk refiner (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphorous groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of phosphorus oxo acid group amount] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0151] <Production Example 10> Ion-exchanged water was added to the phosphorous pulp obtained in Production Example 9 to prepare a slurry with a solid content concentration of 6% by mass. This slurry was treated once with a single-disk refiner (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphorous groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorous oxo acid group] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0152] <Production Example 11> Ion-exchanged water was added to the phosphite pulp obtained in Production Example 9 to prepare a slurry with a solid content concentration of 13% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphite groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid group] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0153] <Production Example 12> Ion-exchanged water was added to the phosphite pulp obtained in Production Example 9 to prepare a slurry with a solid content concentration of 6% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphite groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of phosphorus oxo acid group amount] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0154] <Production Example 13> A phosphorylated pulp was obtained by the same treatment as in Production Example 1, except that the pulp was replaced with hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd. Ion exchange water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 6 mass%. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0155] <Production Example 14> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 13, except that the slurry was prepared so that the solids concentration of the phosphorylated pulp obtained in Production Example 13 was 13 mass %.

[0156] <Production Example 15> A similar process was carried out to obtain a TEMPO oxidized pulp, except that the pulp in Production Example 5 was replaced with hardwood dissolving pulp (undried) manufactured by Oji Paper Co., Ltd. Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry having a solid content concentration of 13% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.

[0157] <Production Example 16> A similar process was carried out to obtain a hypophosphite pulp, except that the pulp in Production Example 9 was replaced with hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd. Ion exchange water was added to the obtained hypophosphite pulp to prepare a slurry having a solid content concentration of 6 mass%. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphorous groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of phosphorus oxo acid group amount] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0158] <Production Example 17> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 16, except that the slurry was prepared so that the solids concentration of the phosphorous pulp obtained in Production Example 16 was 13 mass %.

[0159] <Production Example 18> [Pre-hydrolysis] 300 g of bone-dry softwood chips were collected and soaked in 10 L of tap water overnight. The chips were then removed and sieved through a 400-mesh sieve, and filtered. The dehydrated chips were placed in a 2.5 L autoclave, and tap water was added to the chips so that the liquid mass ratio (when the mass of the bone-dry chips was taken as 1) was 3. The chips were then heated at 165°C for 30 minutes to carry out prehydrolysis. The P factor at this time was 380. [Cooking] After prehydrolysis, the waste gas was removed from the degassing cock of the autoclave, and after confirming that the pressure inside the autoclave had become 0, the treated chips were emptied through a 400-mesh sieve and filtered. The filtered chips were placed again in a 2.5-liter autoclave, and cooking liquor was added so that the liquor ratio was 5. Kraft cooking was carried out under the conditions of a cooking temperature of 165°C and a cooking time of 120 minutes. The cooking liquor contained 21% by mass of active alkali relative to the bone dry mass of the chips, and the sulfidity was 28%. After cooking, the black liquor and pulp were separated, and the pulp was refined using a flat screen equipped with an 8-cut screen plate to obtain a cooked pulp. [bleaching] After the cooking, 70 g of the pulp was collected in terms of bone dry mass, and 2.0% by mass of caustic soda was added to the total mass of the bone dry pulp, and then the pulp concentration was adjusted to 10% by mass by diluting with ion-exchanged water. This slurry was placed in an indirect heating autoclave, and 99.9% compressed oxygen gas was injected to set the gauge pressure to 0.5 MPa, and oxygen exposure was performed at 100°C for 60 minutes. After completion of oxygen exposure, the pressure was reduced until the gauge pressure was 0.05 MPa or less, and the pulp was removed from the autoclave, washed with 7 liters of ion-exchanged water, and then dehydrated. In this way, oxygen-exposed pulp was obtained. After the oxygen exposure, 60 g of the pulp was collected by bone dry weight, placed in a plastic bag, and ion-exchanged water was added to adjust the pulp concentration to 10% by weight. Then, 1.8% by weight of chlorine dioxide was added to the total weight of the bone dry pulp, and the mixture was immersed in a thermostatic water bath at 70°C for 70 minutes (D0 stage treatment). The pulp obtained after the D0 stage treatment was diluted to 3% by weight with ion-exchanged water, and then dehydrated and washed with a Buchner funnel. The pulp after the D0 stage treatment was placed in a plastic bag, and ion-exchanged water was added to adjust the pulp concentration to 10% by weight, and then caustic soda was added to 1.0% by weight and hydrogen peroxide was added to 0.3% by weight with respect to the total weight of the bone dry pulp, and mixed well. Then, the mixture was immersed in a thermostatic water bath at 70°C for 100 minutes to perform the E / P stage treatment. The pulp obtained was diluted to 3% by weight with ion-exchanged water, and then dehydrated and washed with a Buchner funnel. The pulp after the E / P stage treatment was placed in a plastic bag and adjusted to a pulp concentration of 10% by mass using ion-exchanged water, after which 0.3% by mass of chlorine dioxide was added relative to the total mass of the bone-dry pulp, and the pulp was immersed in a thermostatic water bath at 70° C. for 80 minutes to perform a D1 stage bleaching treatment. The resulting pulp was diluted to 3% by mass with ion-exchanged water, and then dehydrated and washed using a Buchner funnel to obtain bleached pulp. [Phosphorylation] This bleached pulp was used and treated in the same manner as in Production Example 1 to obtain phosphorylated pulp. [Defibrilization] Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 6% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0160] <Production Example 19> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 18, except that the slurry was prepared so that the solids concentration of the phosphorylated pulp obtained in Production Example 18 was 13 mass%.

[0161] <Production Example 20> A TEMPO oxidized pulp was obtained by the same treatment as in Production Example 5, except that the bleached pulp of Production Example 18 was used. Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid content concentration of 6 mass%. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion containing fine fibrous cellulose. The amount of carboxy groups measured by the measurement method described below was 1.30 mmol / g.

[0162] <Production Example 21> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 20, except that the slurry was prepared so that the solids concentration of the TEMPO oxidized pulp obtained in Production Example 20 was 13 mass %.

[0163] <Production Example 22> A phosphorous pulp was obtained by the same treatment as in Production Example 9, except that the bleached pulp of Production Example 18 was used. Ion-exchanged water was added to the obtained phosphorous pulp to prepare a slurry having a solid content concentration of 13% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphorous groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorous oxo acid group] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0164] <Production Example 23> A phosphorylated pulp was obtained by the same treatment as in Production Example 1, except that the pulp in Production Example 1 was replaced with hardwood kraft pulp (dry sheet) manufactured by Cenibra. Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 6 mass%. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0165] <Production Example 24> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 23, except that the slurry was prepared so that the solids concentration of the phosphorylated pulp obtained in Production Example 23 was 13 mass%.

[0166] <Production Example 25> The raw material pulp of Production Example 5 was hardwood kraft pulp (dry sheet) manufactured by Cenibra, to which ion-exchanged water was added to prepare a slurry with a pulp concentration of 2% by mass. The mixture was thoroughly stirred at 4000 rpm in a disperser to prepare a pulp slurry, which was then thoroughly dehydrated in a mesh bag to obtain wet pulp. The obtained wet pulp was treated in the same manner as in Production Example 5 to obtain TEMPO oxidized pulp. Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid concentration of 6% by mass. This slurry was treated once with a wet type atomizer (Starburst manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion containing fine fibrous cellulose. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.

[0167] <Production Example 26> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 25, except that the slurry was prepared so that the solids concentration of the TEMPO oxidized pulp obtained in Production Example 25 was 13 mass%.

[0168] <Production Example 27> A phosphorous pulp was obtained by the same treatment as in Production Example 9, except that the raw pulp in Production Example 9 was a hardwood kraft pulp (dry sheet) manufactured by Cenibra. Ion-exchanged water was added to the obtained phosphorous pulp to prepare a slurry having a solid content concentration of 6 mass%. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphorous groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of phosphorus oxo acid group amount] below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.

[0169] <Production Example 28> A fibrous cellulose dispersion containing fine fibrous cellulose was obtained in the same manner as in Production Example 27, except that the slurry was prepared so that the solids concentration of the phosphorous pulp obtained in Production Example 27 was 13 mass %.

[0170] <Production Example 29> The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 208 g / m) manufactured by Oji Paper. 2 A sheet-like pulp (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated and measured in accordance with JIS P 8121) was used. This raw pulp was subjected to a sulfation treatment as follows. First, a mixed aqueous solution of amidosulfuric acid and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the amount to 38 parts by mass of amidosulfuric acid, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 20 minutes to introduce sulfate groups into the cellulose in the pulp, thereby obtaining a sulfated pulp.

[0171] Next, the obtained sulfated pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly stirring the pulp dispersion obtained by pouring 10 L of ion-exchanged water into 100 g (absolute dry weight) of sulfated pulp so that the pulp was uniformly dispersed, followed by filtering and dehydrating the pulp. The washing was terminated when the electrical conductivity of the filtrate reached 100 μS / cm or less. Next, the sulfated pulp after washing was neutralized as follows. First, the sulfated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was gradually added while stirring to obtain a sulfated pulp slurry having a pH of 12 to 13. Next, the sulfated pulp slurry was dehydrated to obtain a sulfated pulp that had been subjected to a neutralization treatment. Next, the sulfated pulp after neutralization was subjected to the above washing treatment.

[0172] The infrared absorption spectrum of the sulfated pulp obtained was measured using FT-IR. -1 Absorption due to sulfate groups (sulfone groups) was observed near the nucleus, confirming that sulfate groups (sulfone groups) had been added to the pulp. Furthermore, X-ray diffraction confirmed that the obtained sulfated pulp maintained cellulose type I crystals.

[0173] Ion-exchanged water was added to the obtained sulfated pulp to prepare a slurry with a solid content of 6% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of sulfate groups measured by the measurement method described later in [Measurement of the amount of sulfur oxo acid groups] was 1.47 mmol / g.

[0174] <Example 1> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration 3% by mass, solid content 30 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of the fine fibrous cellulose, and the mixture was stirred at 25° C. in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion.

[0175] The obtained fine fibrous cellulose dispersion was treated three times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion having a fine fibrous cellulose concentration of 3% by mass.

[0176] <Example 2> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration 3 mass%, solid content 30 g), an enzyme-containing solution having an activity of 16500 nkat was added and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then thermally inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0177] <Example 3> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration 3.5 mass%, solid content 35 g), 145 g of sodium hypochlorite solution (effective chlorine concentration 12 mass%) was added and mixed well at room temperature. The sodium hypochlorite addition rate at this time was 0.5 parts by mass per part by mass of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0178] <Example 4> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 5 (solid content concentration 3 mass%, solid content 30 g), ozone was added at a ratio of 0.2 mass parts per mass part of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0179] <Example 5> An enzyme-containing solution having an activity of 16500 nkat was added to 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 5 (solid content concentration 3 mass%, solid content 30 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. A fine fibrous cellulose dispersion was obtained. Next, the temperature was set to 100°C to heat-inactivate the enzyme. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0180] <Example 6> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 5 (solid content concentration 3.5 mass%, solid content 35 g), 145 g of sodium hypochlorite solution (effective chlorine concentration 12 mass%) was added and mixed well at room temperature. The sodium hypochlorite addition rate at this time was 0.5 parts by mass per part by mass of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0181] <Example 7> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 9 (solid content concentration 3 mass%, solid content 30 g), ozone was added at a ratio of 0.2 mass parts per mass part of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0182] <Example 8> An enzyme-containing solution having an activity of 16,500 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 9 (solid content concentration 3% by mass, solid content 30 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3% by mass.

[0183] <Example 9> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 9 (solid content concentration 3.5 mass%, solid content 35 g), 145 g of sodium hypochlorite solution (effective chlorine concentration 12 mass%) was added and mixed well at room temperature. The sodium hypochlorite addition rate at this time was 0.5 parts by mass per part by mass of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 3 mass%.

[0184] <Example 10> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 2 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0185] <Example 11> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 2 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0186] <Example 12> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 6 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0187] <Example 13> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 6 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0188] <Example 14> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 10 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0189] <Example 15> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 10 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0190] <Example 16> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 3 (solid content concentration 13% by mass, solid content 130 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion, thereby obtaining a fine fibrous cellulose dispersion. The obtained fine fibrous cellulose dispersion was further treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0191] <Example 17> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 3 (solid content concentration 13 mass%, solid content 130 g), an enzyme-containing solution having an activity of 71500 nkat was added and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was further treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13 mass%.

[0192] <Example 18> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 7 (solid content concentration 13% by mass, solid content 130 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion, thereby obtaining a fine fibrous cellulose dispersion. The obtained fine fibrous cellulose dispersion was further treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0193] <Example 19> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 7 (solid content concentration 13 mass%, solid content 130 g), an enzyme-containing solution having an activity of 71500 nkat was added and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was further treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13 mass%.

[0194] <Example 20> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 11 (solid content concentration 13 mass%, solid content 130 g), ozone was added at a ratio of 0.2 mass parts per mass part of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion, thereby obtaining a fine fibrous cellulose dispersion. The obtained fine fibrous cellulose dispersion was further treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13 mass%.

[0195] <Example 21> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 11 (solid content concentration 13 mass%, solid content 130 g), an enzyme-containing solution having an activity of 71500 nkat was added and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was further treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13 mass%.

[0196] <Example 22> Ion-exchanged water was added to the phosphorylated pulp obtained in Production Example 1 to prepare a slurry with a solid content concentration of 6% by mass. Ozone was added to 1000 g of this slurry (solid content concentration 6% by mass, solid content 60 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion, thereby obtaining a fibrous cellulose dispersion. The obtained fibrous cellulose dispersion was treated four times with a wet-type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0197] <Example 23> Ion exchange water was added to the phosphorylated pulp obtained in Production Example 1 to prepare a slurry with a solid content concentration of 6% by mass. An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of this slurry (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained slurry was treated once at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then the enzyme treatment was continued. Thereafter, it was treated three times at a pressure of 200 MPa and heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0198] <Example 24> Ion-exchanged water was added to the TEMPO oxidized pulp obtained in Production Example 5 to prepare a slurry with a solid content concentration of 6% by mass. Ozone was added to 1000 g of this slurry (solid content concentration 6% by mass, solid content 60 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion, thereby obtaining a fibrous cellulose dispersion. The obtained fibrous cellulose dispersion was treated four times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0199] <Example 25> Ion-exchanged water was added to the TEMPO oxidized pulp obtained in Production Example 5 to prepare a slurry with a solid content concentration of 6% by mass. An enzyme-containing solution having an activity of 33,000 nkat was added to 1000 g of this slurry (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained slurry was treated once at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then the enzyme treatment was continued. Thereafter, the slurry was treated three times at a pressure of 200 MPa and heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0200] <Example 26> Ion-exchanged water was added to the phosphorus-containing pulp obtained in Production Example 9 to prepare a slurry with a solid content concentration of 6% by mass. Ozone was added to 1000 g of this slurry (solid content concentration 6% by mass, solid content 60 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion, thereby obtaining a fibrous cellulose dispersion. The obtained fibrous cellulose dispersion was treated four times with a wet-type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0201] <Example 27> Ion-exchanged water was added to the phosphorus-substituted pulp obtained in Production Example 9 to prepare a slurry with a solid content concentration of 6% by mass. An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of this slurry (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained slurry was treated once at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then the enzyme treatment was continued. Thereafter, the slurry was treated three times at a pressure of 200 MPa and heat-deactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0202] <Example 28> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 4 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0203] <Example 29> An enzyme-containing liquid having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 4 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0204] <Example 30> Ion-exchanged water was added to the phosphorylated pulp obtained in Production Example 4 to prepare a slurry with a solid content concentration of 7.5% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion containing fine fibrous cellulose, and then 250 g of sodium hypochlorite solution (effective chlorine concentration of 12% by mass) was added to 1000 g of this dispersion (solid content concentration of 7.5% by mass, solid content of 75 g) and mixed well at room temperature. The sodium hypochlorite addition rate at this time was 0.4 parts by mass per part by mass of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0205] <Example 31> Ozone was added to 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 8 (solid content concentration 6% by mass, solid content 60 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0206] <Example 32> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 8 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0207] <Example 33> Ion-exchanged water was added to the TEMPO oxidized pulp obtained in Production Example 8 to prepare a slurry with a solid content concentration of 7.5% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion containing fine fibrous cellulose, and then 250 g of sodium hypochlorite solution (effective chlorine concentration of 12% by mass) was added to 1000 g of this dispersion (solid content concentration of 7.5% by mass, solid content of 75 g) and stirred at room temperature. The sodium hypochlorite addition rate at this time was 0.4 parts by mass per part by mass of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0208] <Example 34> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 12 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0209] <Example 35> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 12 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0210] <Example 36> Ion-exchanged water was added to the hypophosphite pulp obtained in Production Example 12 to prepare a slurry with a solid content concentration of 7.5% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fibrous cellulose dispersion containing fine fibrous cellulose, and then 250 g of sodium hypochlorite solution (effective chlorine concentration of 12% by mass) was added to 1000 g of the fine fibrous cellulose dispersion (solid content concentration of 7.5% by mass, solid content of 75 g) and stirred at room temperature. The sodium hypochlorite addition rate at this time was 0.4 parts by mass per part by mass of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0211] <Example 37> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 13 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0212] <Example 38> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 18 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0213] <Example 39> An enzyme-containing solution having an activity of 71,500 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 14 (solid content concentration 13% by mass, solid content 130 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated four times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0214] <Example 40> Ozone was added to 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 19 (solid content concentration 13% by mass, solid content 130 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-deactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0215] <Example 41> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 20 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0216] <Example 42> An enzyme-containing solution having an activity of 71,500 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 15 (solid content concentration 13% by mass, solid content 130 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated four times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0217] <Example 43> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 16 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0218] <Example 44> An enzyme-containing solution having an activity of 71,500 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 22 (solid content concentration 13% by mass, solid content 130 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 550 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0219] <Example 45> In 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 23 (solid content concentration 6% by mass, solid content 60 g), ozone was added at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0220] <Example 46> To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 24 (solid content concentration 13 mass%, solid content 130 g), an enzyme-containing solution having an activity of 104000 nkat was added and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 800 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13 mass%.

[0221] <Example 47> An enzyme-containing solution having an activity of 48,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 25 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 800 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0222] <Example 48> Ozone was added to 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 26 (solid content concentration 13% by mass, solid content 130 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-deactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0223] <Example 49> Ozone was added to 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 27 (solid content concentration 6% by mass, solid content 60 g) at a ratio of 0.2 parts by mass per part by mass of fine fibrous cellulose, and the mixture was stirred at 25°C in a sealed container and allowed to stand for 30 minutes. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The obtained fine fibrous cellulose dispersion was treated three times with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa, and then heat-deactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0224] <Example 50> An enzyme-containing solution having an activity of 104,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 28 (solid content concentration 13% by mass, solid content 130 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 800 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was treated four times at a pressure of 200 MPa with a wet type micronizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and then heat-inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0225] <Example 51> An enzyme-containing solution having an activity of 33,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 4 (solid content concentration 6% by mass, solid content 60 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The enzyme was then thermally inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0226] <Example 52> An enzyme-containing solution having an activity of 71,500 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 3 (solid content concentration 13% by mass, solid content 130 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added at this time was 550 nkat per 1 g of fine fibrous cellulose. The enzyme was then thermally inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0227] <Example 53> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 7 was used.

[0228] <Example 54> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 11 was used.

[0229] <Example 55> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 14 was used.

[0230] <Example 56> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 15 was used.

[0231] <Example 57> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 17 was used.

[0232] <Example 58> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 19 was used.

[0233] <Example 59> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 21 was used.

[0234] <Example 60> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 52, except that the fine fibrous cellulose dispersion obtained in Production Example 22 was used.

[0235] <Example 61> An enzyme-containing solution having an activity of 104,000 nkat was added to 1,000 g of the fine fibrous cellulose dispersion obtained in Production Example 24 (solid content concentration 13% by mass, solid content 130 g) and subjected to enzyme treatment at a temperature of 50°C. The amount of enzyme added was 800 nkat per 1 g of fine fibrous cellulose. The obtained fine fibrous cellulose dispersion was thermally inactivated at 100°C to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 13% by mass.

[0236] <Example 62> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 61, except that the fine fibrous cellulose dispersion obtained in Production Example 26 was used.

[0237] <Example 63> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 61, except that the fine fibrous cellulose dispersion obtained in Production Example 28 was used.

[0238] <Example 64> A fine fibrous cellulose dispersion was obtained in the same manner as in Example 29, except that the fine fibrous cellulose dispersion obtained in Production Example 29 was used.

[0239] It was confirmed by X-ray diffraction that the fine fibrous cellulose of Examples 1 to 64 maintained cellulose type I crystals. Furthermore, when the fiber width of these fine fibrous celluloses was measured using a transmission electron microscope, all of them contained fine fibrous cellulose with a diameter of 3 to 5 nm.

[0240] <Comparative Example 1> Ion-exchanged water was added to softwood bleached kraft pulp (NBKP) to prepare a slurry with a solid content of 6% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. The concentration of fine fibrous cellulose in this fine fibrous cellulose dispersion was 6% by mass.

[0241] X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The number-average fiber width of the fine fibrous cellulose contained in this dispersion was 1000 nm or less.

[0242] <Comparative Example 2> Ion-exchanged water was added to the phosphorylated pulp obtained in Production Example 1 to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated five times at a pressure of 200 MPa using a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0243] <Comparative Example 3> The fine fibrous cellulose dispersion obtained in the same manner as in Comparative Example 2 was concentrated at 50°C until the concentration of the fine fibrous cellulose reached 6% by mass, to obtain a fibrous cellulose dispersion liquid containing fine fibrous cellulose. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid group] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.

[0244] <Comparative Example 4> The dispersion of fine fibrous cellulose obtained in the same manner as in Comparative Example 2 was diluted to 0.4% by mass. 1 g of calcium chloride was added as a thickening agent to 100 mL of the diluted solution to gel it, and after filtration, it was squeezed with filter paper. After immersion in 100 mL of 0.1 N hydrochloric acid aqueous solution for 30 minutes, it was filtered to obtain a concentrate with a solid concentration of 20% by mass. The obtained concentrate was diluted with ion-exchanged water so that the concentration was 6%, and then stirred, but a uniform dispersion was not obtained.

[0245] <Measurement> [Measurement of phosphorus oxoacid group content] The amount of phosphorus oxoacid groups in the fine fibrous cellulose was measured by treating a fibrous cellulose-containing slurry with an ion exchange resin after diluting a fine fibrous cellulose dispersion containing the target fine fibrous cellulose with ion exchange water to a content of 0.2 mass%, and then titrating the slurry with an alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution every 5 seconds to the fibrous cellulose-containing slurry after the ion exchange resin treatment, while measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (the derivative value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the alkali addition is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 2). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated, and this value was taken as the amount of phosphorus oxoacid groups (mmol / g).

[0246] [Measurement of Carboxy Group Amount] The amount of carboxy groups in the fine fibrous cellulose was measured by treating a fibrous cellulose-containing slurry with an ion exchange resin after diluting a fine fibrous cellulose dispersion containing the target fine fibrous cellulose with ion exchange water to a content of 0.2 mass%, and then titrating the slurry with an alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. Also, in the titration using an alkali, while adding 50 μL of a 0.1 N aqueous sodium hydroxide solution once every 30 seconds to the fibrous cellulose-containing slurry after treatment with an ion exchange resin, the change in the value of the electrical conductivity exhibited by the slurry was measured. The amount of carboxyl groups (mmol / g) was calculated by dividing the amount of alkali (mmol) required in the region corresponding to the first region shown in FIG. 3 in the measurement results by the solid content (g) in the slurry to be titrated.

[0247] [Measurement of the amount of sulfur oxoacid groups] After wet ashing the obtained fibrous cellulose using perchloric acid and concentrated nitric acid, it was diluted at an appropriate magnification and the amount of sulfur was measured by ICP emission analysis. The value obtained by dividing this amount of sulfur by the absolutely dry mass of the tested fibrous cellulose was defined as the amount of sulfur oxoacid groups (unit: mmol / g).

[0248] [Measurement of the viscosity of the microfibrillated cellulose dispersion by a rheometer] The viscosities of the microfibrillated cellulose dispersions obtained in Examples 1 to 64 and Comparative Examples 1 to 3 were measured using a rheometer (RheoStress6000 manufactured by HAAKE). Regarding the shear rate, it was changed under the following conditions. Measurement temperature: 23°C Measurement jig: Cone plate (diameter 40 mm, angle 1°) Shear rate: 0.001 to 1000 sec -1 Number of data points: 100 points Data distribution: Log interval Measurement time: 5 minutes

[0249] [Calculation of the TI value] The viscosity of the microfibrillated cellulose dispersion was measured by the method described above, and the value of the viscosity (η1) measured under the condition of a shear rate of 1 sec -1 was divided by the value of the viscosity (η2) measured under the condition of a shear rate of 1000 sec -1 to obtain a value defined as the thixotropic index value (TI value) of the thickener. That is, the TI value was calculated by the following formula. TI value = η1 / η2 η1: Shear rate 1sec -1 Viscosity measured under the conditions η2: Shear rate 1000sec -1 Viscosity measured under the conditions

[0250] [Measurement of specific viscosity and polymerization degree of fine fibrous cellulose] The specific viscosity and degree of polymerization of the fine fibrous cellulose were measured according to Tappi T230. That is, the fine fibrous cellulose to be measured was dispersed in a dispersion medium to measure the viscosity (referred to as ηX), and the blank viscosity (referred to as η0) was measured using only the dispersion medium, and then the specific viscosity (ηsp) and intrinsic viscosity ([η]) were measured according to the following formula. ηsp=(ηX / η0)-1 [η]=ηsp / (c(1+0.28×ηsp)) Here, c in the formula represents the concentration of cellulose fibers at the time of viscosity measurement. Furthermore, the degree of polymerization (DP) of the fine fibrous cellulose was calculated from the following formula. DP = 1.75 × [η] Since this degree of polymerization is an average degree of polymerization measured by a viscosity method, it is sometimes called the "viscosity average degree of polymerization."

[0251] [Measurement of haze of fine fibrous cellulose dispersion] The haze of the fine fibrous cellulose dispersion obtained in Examples 1 to 64 and Comparative Examples 1 to 3 was measured by diluting the fine fibrous cellulose dispersion with ion-exchanged water to 0.2% by mass, and then measuring the haze with a haze meter (Murakami Color Research Laboratory, HM-150) using a glass cell for liquids with an optical path length of 1 cm (Fujiwara Manufacturing, MG-40, reverse optical path) in accordance with JIS K 7136:2000. The zero point measurement was performed with ion-exchanged water placed in the same glass cell. The dispersion to be measured was left to stand for 24 hours in an environment of 23°C and relative humidity of 50% before the measurement. The liquid temperature of the dispersion during the measurement was 23°C.

[0252] <Evaluation> [Visual evaluation of fine fibrous cellulose dispersion] The fine fibrous cellulose dispersions obtained in Examples 1 to 64 and Comparative Examples 1 to 3 were each diluted with ion-exchanged water to a solid content concentration of 3% by mass. Next, a degassing treatment was performed using a planetary centrifugal super mixer (ARE-250, manufactured by Thinky Corporation). Thereafter, the transparency of the dispersions was evaluated visually. As the evaluation criteria, the dispersions were placed in a glass cell, and a piece of paper with 11-point characters written on one side was placed on it, and the evaluation was performed according to the following criteria. A: When viewed from the other side, the characters are clearly legible. B: Somewhat blurry, but the text is legible C: The text is blurry and difficult to read, but you can see that it is there. D: Cannot be deciphered at all

[0253] <Preparation of evaluation sheet> Polyethylene oxide (PEO-3P, manufactured by Sumitomo Seika Chemicals Co., Ltd.) was added to ion-exchanged water to a concentration of 5% by mass, and dissolved by stirring to obtain an aqueous polyethylene oxide solution. Next, the fine fibrous cellulose dispersions obtained in Examples 1 to 64 and Comparative Examples 1 to 3 were mixed with the above aqueous polyethylene oxide solution to a ratio of fine fibrous cellulose (solid content):polyethylene oxide (solid content) = 100 parts by mass:20 parts by mass. In addition, the coating liquid was appropriately diluted with ion-exchanged water to obtain a solid content concentration of 2.5% by mass in Examples 1 to 9, 5% by mass in Examples 10 to 15, 22 to 38, 41, 43, 45, 47, 49, 51, and Comparative Examples 1, 3, and 4, 10% by mass in Examples 16 to 21, 39, 40, 42, 44, 46, 48, 50, and 52 to 64, and 1.5% by mass in Comparative Example 2. Next, the coating liquid was measured so that the finished thickness of the obtained sheet (layer composed of the solid content of the coating liquid) was 40 μm, and the coating liquid was applied to a commercially available polycarbonate plate and dried for 30 minutes in a dryer at 100 ° C. In addition, a metal frame for damming (metal frame with inner dimensions of 180 mm × 180 mm and height of 5 cm) was placed on the polycarbonate plate so as to obtain a predetermined basis weight. Next, the dried sheet was peeled off from the polycarbonate plate to obtain a fine fibrous cellulose-containing sheet.

[0254] [Sheet transparency evaluation] The haze of the obtained fine fibrous cellulose-containing sheet was measured in accordance with JIS K 7136:2000 using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory). The haze of the sheet was judged according to the following criteria: When the haze of the sheet was less than 95%, the transparency was judged to be good. A: 0% or more and less than 5% B: 5% or more but less than 30% C: 30% or more but less than 95% D: 95% or more

[0255] [Evaluation of sheet curl] The fine fibrous cellulose-containing sheet obtained by the above-mentioned method was cut into a test piece having a width of 15 mm and a length of 130 mm. As shown in FIG. 1, the end including one short side of the test piece 50 was supported by a curl test jig 55 having a width of 30 mm, a length of 30 mm, and a height of 25 mm (a test piece having a length of 100 mm was exposed from the jig), and the test piece was placed on a horizontal table in an environment of a temperature of 23° C. and a relative humidity of 50% so that the width direction of the test piece was perpendicular to the table (so that the longitudinal direction of the test piece was parallel to the table). Then, the curl width of the end of the test piece 50 was measured and defined as the curl width C0 (the distance of C0 in FIG. 1). After leaving it for 24 hours, the curl width was measured again and defined as C1 (the distance of C1 in FIG. 1), and C1-C0 was defined as the curl amount. The amount of curl was judged according to the following criteria. When the amount of curl was 25 mm or less, it was judged that the curl resistance was good. A: 5mm or less B: More than 5mm and less than 25mm C: More than 25mm

[0256] [Table 1]

[0257] [Table 2]

[0258] [Table 3]

[0259] [Table 4]

[0260] [Table 5]

[0261] [Table 6]

[0262] [Table 7]

[0263] [Table 8]

[0264] In the examples, a high-concentration fine fibrous cellulose dispersion was obtained, and a sheet with suppressed curling was formed from such a dispersion. This is thought to be because forming a sheet from a high-concentration fine fibrous cellulose dispersion can reduce the amount of moisture carried in, thereby suppressing thermal shrinkage during drying. In addition, in Comparative Example 4, a uniform sample could not be prepared, and viscosity and other measurements could not be performed. [Explanation of symbols]

[0265] 50 test pieces 55 Test fixture

Claims

1. A dispersion containing fibrous cellulose having a fiber width of 1000 nm or less and having an ionic substituent, The content of the fibrous cellulose is 3.0% by mass or more based on the total mass of the dispersion, The haze of the dispersion liquid is 50% or less when the concentration of the dispersion liquid is 0.2% by mass, A dispersion in which the TI value of the dispersion calculated under the following condition (a) is 1 or more and 80,000 or less, the viscosity (η1) of the dispersion measured under the following condition (a) is 1 Pa s or more and 5,000 Pa s or less, and the viscosity (η2) of the dispersion measured under the following condition (a) is 0.007 Pa s or more and 100 Pa s or less; Condition (a): A rheometer equipped with a cone plate (diameter 40 mm, angle 1°) was used, and the shear rate of the dispersion was 1 sec at a measurement temperature of 23° C. and a measurement time of 5 minutes. -1 The viscosity (η1) under the condition of and the shear rate of the dispersion liquid at 1000 sec -1 The viscosity (η2) under the above conditions is measured, and the TI value is calculated according to the following formula. TI value = η1 / η2

2. The dispersion according to claim 1 , wherein the content of the fibrous cellulose is 4.0% by mass or more based on the total mass of the dispersion.

3. The dispersion according to claim 1 , wherein the content of the fibrous cellulose is 5.0% by mass or more based on the total mass of the dispersion.

4. The dispersion according to claim 1 , wherein the content of the fibrous cellulose is 6.0% by mass or more based on the total mass of the dispersion.

5. The dispersion according to any one of claims 1 to 4, wherein the ionic substituent is at least one selected from the group consisting of a phosphorus oxoacid group, a substituent derived from a phosphorus oxoacid group, a sulfur oxoacid group, and a substituent derived from a sulfur oxoacid group.

6. A sheet formed from the dispersion of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Cellulose fiber and manufacturing method thereof

    JP2009298972A

  • Fine fibrous cellulose, method for producing the same, fine fibrous cellulose dispersion, and non-woven fabric

    JP2013253200A

  • Fine fibrous cellulose

    JP2014034673A

  • Manufacturing method of fine fibrous cellulose re-dispersion slurry and fine fibrous cellulose re-dispersion slurry

    JP2017052943A

  • Fibrous cellulose-containing composition, method of producing the same, and film

    JP2019026651A